Investigating The Necessity of Learning Module For Japanese Language Acquisition Among Learners at USIM - Margaret Anthoney; Nurhasma Muhamad Saad; Yee Chin Yip (Universiti Sains Islam Malaysia, 2025)
Al-Azkiyaa - International Journal of Language and Education, Volume 4 Issue 1 Page (153–161)